Newborn Mortality in the United States - Donna Davis (EDIS)
"While the United States boasts some of the finest healthcare facilities and services known to humankind, the country also has one of the highest newborn mortality rates in the industrialized world. In fact, according to the World Health Organization, the U.S. is tied for second to last (with Hungary, Malta, Poland, and Slovakia), with 5 newborn deaths per 1,000 live births (World Health Organization 2005)." This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, August 2012.